Improving Document Management and Information Flow in a Railway Signalling Projects Operation - Erubami, Paul O. (2010)
ABSTRACT The availability and application of quality information plays a pivotal role in the success of engineering, design and project management operations in hi-tech and knowledge-based industries, such as those involved in providing engineering solutions for signalling to the railway industry. This research Project has as its stated purpose to evaluate the capabilities and extents of deployment of current document management systems, assess the document management needs of Signalling Solutions Ltd, and make recommendations based on gap analysis between needs, available systems and business requirements. The objective is to produce a workable program for the planning, selection and implementation of an enterprise content management system for the management of information assets by Signalling Solutions Ltd, a UK provider of engineering solutions for railways signalling. The study presents first an understanding of the current situation of the business, a vision of the ideal situation with regards to document and information management and then proceeds to chart a possible path to improve on the people, processes and technology required to achieve the future state. The methodology adopted include the use of literature review of relevant articles published in reputable journals and books to describe precedent, current and future trends in the industry. Surveys are combined with interviews for primary data collection, after which mixed-methods evaluation techniques are then employed to analyse and present the case study research findings. This study shows that the large volumes and types of data, strict regulatory and contractual obligations and the need for high level information security in the rail industry calls for investment in an effective document management system. However, the selection of a particular vendor or supplier’s electronic document or enterprise information management system based on functionality, though very significant, comes secondary to the user and organisational issues involved in the effective implementation of such systems for overall success.